Fuchs' Endothelial Corneal Dystrophy and RNA Foci in Patients With Myotonic Dystrophy - Mootha, V. Vinod; Hansen, Brock; Rong, Ziye; Mammen, Pradeep P.; Zhou, Zhengyang; Xing, Chao; Gong, Xin (Investigative ophthalmology & visual science, 2017)
The most common cause of Fuchs' endothelial corneal dystrophy (FECD) is an intronic CTG repeat expansion in TCF4. Expanded CUG repeat RNA colocalize with splicing factor, muscleblind-like 1 (MBNL1), in nuclear foci in endothelium as a molecular hallmark. Myotonic dystrophy type 1 (DM1) is a neuromuscular disorder caused by a CTG repeat expansion in the 3'-untranslated region (UTR) of DMPK. In this study, we examine for RNA-MBNL1 foci in endothelial cells of FECD subjects with DM1, test the hypothesis that DM1 patients are at risk for FECD, and determine prevalence of TCF4 and DMPK expansions in a FECD cohort. Using FISH, we examined for nuclear RNA-MBNL1 foci in endothelial cells from FECD subjects with DM1. We examined 13 consecutive unrelated DM1 patients for FECD using slit-lamp and specular microscopy. We genotyped TCF4 and DMPK repeat polymorphisms in a FECD cohort of 317 probands using short-tandem repeat and triplet repeat-primed PCR assays. We detected abundant nuclear RNA foci colocalizing with MBNL1 in endothelial cells of FECD subjects with DM1. Six of thirteen DM1 patients (46%) had slit-lamp and specular microscopic findings of FECD, compared to 4% disease prevalence (P = 5.5 × 10-6). As expected, 222 out of 317 (70%) FECD probands harbored TCF4 expansion, while one subject harbored DMPK expansion without prior diagnosis of DM1. Our work suggests that DM1 patients are at risk for FECD. DMPK mutations contribute to the genetic burden of FECD but are uncommon. We establish a connection between two repeat expansion disorders converging upon RNA-MBNL1 foci and FECD.